High diversity of fungal ecological groups from ice-free pristine and disturbed areas in the Fildes Peninsula, King George Island, Antarctica - Sigisfredo Garnica; Genaro Soto-Rauch; Ellen M. Leffler; Christian Núñez; Jonhatan Gómez-Espinoza; Enzo Romero; Ramón Ahumada-Rudolph; Jaime R. Cabrera-Pardo (PLoS ONE, 2025)
Ice-free areas are habitats for most of Antarctica’s terrestrial biodiversity. Although fungal communities are an important element of these habitats, knowledge of their assemblages and ecological functions is still limited. Herein, we investigated the diversity, composition, and ecological functionality of fungal communities inhabiting sediments from ice-free areas across pristine and anthropogenically impacted sites in the Fildes Peninsula on King George Island, Antarctica. Samples were collected from both pristine and disturbed areas. We used the internal transcribed spacer (ITS1) region via Illumina sequencing of 34 sediment samples for fungal identification. The Ascomycota (14.6%) and Chytridiomycota (11.8%) were the most dominant phyla, followed by Basidiomycota (8.1%), Rozellomycota (7.0%), Mucoromycota (4.0%), while 34.9% of the fungal diversity remained unidentified. From a total of 1073 OTUs, 532 OTUs corresponded to 114 fungal taxa at the genus level, and 541 OTUs remained unassigned taxonomically. The highest diversity, with 18 genera, was detected at site A-3. At the genus level, there was no preference for either pristine or disturbed sites. The most widely distributed genera were Betamyces (Chytridiomycota), occurring in 29 of the 34 sites, and Thelebolus (Ascomycota), detected in 8 pristine sites and 7 disturbed sites. The Glomeraceae gen. incertae sedis was more common in disturbed sites. A total of 23 different ecological guilds were recorded, with the most abundant guilds being undefined saprotrophs, plant pathogens, plant saprotrophs, pollen saprotrophs, and endophytes. The fungal communities did not show significant differences between pristine and disturbed sites, suggesting that the anthropogenic impact is either not too intense or prolonged, that the spatial distance between the sampled sites is small, and/or that the environmental factors are similar. Although our study revealed a high fungal diversity with various ecological specializations within these communities, nearly one-third of the diversity could not be assigned to any specific taxonomic category. These findings highlight the need for further taxonomic research on fungal species inhabiting ice-free areas. Without identifying the species present, it is difficult to assess potential biodiversity loss due to environmental changes and/or human activities.